Separation of cancer cells from white blood cells by pinched flow fractionation. Issue 24 (29th October 2015) - Pødenphant, Marie; Ashley, Neil; Koprowska, Kamila; Mir, Kalim U.; Zalkovskij, Maksim; Bilenberg, Brian; Bodmer, Walter; Kristensen, Anders; Marie, Rodolphe
Abstract : A pinched flow fractionation (PFF) device is used to separate cancer cells (red) from white blood cells (blue) at efficiencies above 90% for both cell types. Abstract : In this paper, the microfluidic size-separation technique pinched flow fractionation (PFF) is used to separate cancer cells from white blood cells (WBCs). The cells are separated at efficiencies above 90% for both cell types. Circulating tumor cells (CTCs) are found in the blood of cancer patients and can form new tumors. CTCs are rare cells in blood, but they are important for the understanding of metastasis. There is therefore a high interest in developing a method for the enrichment of CTCs from blood samples, which also enables further analysis of the separated cells. The separation is challenged by the size overlap between cancer cells and the 10 6 times more abundant WBCs. The size overlap prevents high efficiency separation, however we demonstrate that cell deformability can be exploited in PFF devices to gain higher efficiencies than expected from the size distribution of the cells.